Comparative Performance AODV-ANT and AOMDV-ANT in BlackHole - Mayang, Ajeng; Galih, Savitri (International Journal of Engineering and Technology, 2018)
In this paper, we simulate the black hole attack to compare performance AODV-ANT and AOMDV-ANT to support the advance of the node communications to deliver a good management. In our simulation, the result shows AODV-ANT has decrease packets receive in Blackhole attack comparing without black hole until 0.03%, and while in AOMDV-ANT decrease until 0.47%. But, in throughput, AOMDV-ANT is better than AODV-ANT. The result is AOMDV-ANT has decrease throughput in Blackhole attack comparing without black hole until 0.93%, and while in AODV-ANT decrease until 1.85%. Then, in packet delivery ratio (PDR), AODV-ANT has decrease PDR in Blackhole attack comparing without black hole until 10.357%, and while in AOMDV-ANT decrease until 13.57%. In simulation performed, the impact of the black hole can be seen in the PDR. This occurs because of the random node mobility. For our simulations using NS-2:35 as a tool.Â